Development and validation of high-resolution melting assays for the detection of potentially virulent strains of Escherichia coli O103 and O121. (September 2022) - Velez, Frank J.; Bosilevac, Joseph M.; Delannoy, Sabine; Fach, Patrick; Nagpal, Ravinder; Singh, Prashant
Abstract: Virulent strains of Shiga toxin-producing Escherichia coli (STEC) serogroups O103 and O121 are considered adulterants in beef. Two high-resolution melting (HRM) real-time PCR assays were standardized for the specific detection and discrimination of potentially virulent and avirulent strains of E. coli O103 and O121. The O103 HRM assay offered the possibility to distinguish clearly STEC O103:H2 from STEC O103:H25. The two standardized assays were extensively validated using 215 pure culture strains, laboratory inoculated food samples, and naturally contaminated beef (n = 84) and pork (n = 84) enrichments collected from the red meat surveillance program. Both HRM assays showed 100% inclusivity and exclusivity using pure culture strains and enriched spiked food samples. Data from this study shows the ability of the standardized assays to specifically detect the strains of each target serogroup and, most importantly, to differentiate the strains present into potentially virulent or avirulent groups. The assays standardized in this study can be helpful for food surveillance programs and help mitigate product loss due to the presence of avirulent strains lacking crucial virulence genes ( stx and eae ). Graphical abstract: Image 1 Highlights: Two high-resolution melting assays for detection of E. coli O103 and O121. Assays specifically identify STEC and non-STEC strains of O103 and O121. The 103 HRM assay can differentiate between STEC O103:H2 and STEC O103:H25 strains. Two HRM assays can minimize product loss due to the presence non-STEC strains.